I am currently trying to understand functional dependencies and their properties. I am looking at an example, but when I try to apply the rules I can't see to get the same answers. The question is:
Question: Given a relation T(A,B, C,D) and functional dependencies AB -> C, BC -> D,CD -> A AD -> B What FD’s follow from the given FD’s?
Answer: AD -> CD,AD -> BC,CD -> AB.
When applying the properties of functional dependencies I can't even see how they get the first answer (AD -> CD). If anyone could give me an idea of how we get to the first answer, maybe I can solve the rest myself.
PS: This is NOT homework (as I already have the answer!), but I am revising for an important exam and I need to understand these concepts.